METHODOLOGICAL BASES OF FORMATION NATIONAL QUALIFICATIONS FRAMEWORK OF RUSSIA - Vera I. Skorobogatova (Статистика и экономика)
The author examines the need for the approval of the National Qualiﬁcations Framework of the Russian Federation which is necessary to ensure comparability of national qualiﬁcations with qualiﬁcations issued in other countries. Also, the presence of the NQF is an important toolfor the integration of Russian educationin the European Higher Education Area.The article presents the author’s detailed analysis of the levels of qualiﬁ cations in the European Qualiﬁ cations Framework and the establishment of compliance withthese paths levels in the Russian systemof education and training.